Pemakaian Bahasa Campuran (Code Mixing) pada Interaksi Remaja di Media Sosial: Kajian Sosiolinguistik - Annisa Nurfebriani; Intan Sulistiyowati (PT. Saha Kreasi Indonesia, 2025)
The phenomenon of using language mixing (code mixing) in interacting on social media by teenagers continues to increase as the culture of digital communication develops. This research aims to explain various forms of mixed language use as well as identify functions and social factors that affect their use in conversations and uploads by teenagers on Instagram, TikTok, Twitter, and WhatsApp platforms. The method used is a qualitative descriptive approach by indirectly observing and recording the speech of teenagers in comments, captions, and online conversations. The results show that the most commonly used forms of mixed languages are insertion (65%), then alternation (25%), and intra-lexical hybrid (10%). The use of mixed languages is used to express self-identity, strengthen the sense of togetherness in the peer group (in-group identity), create a modern and expressive impression, and increase the effectiveness of communication. Factors that affect include the frequency of using social media, the influence of peers, exposure to global content, and English language skills. In conclusion, language mixing is a communication strategy that reflects the linguistic identity and interaction style of adolescents in the digital era, not just a form of deviation from the standard language rules.